2012
DOI: 10.1016/j.ijggc.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and systematic experimental investigation of mass transfer in supported palladium-based membrane separators

Abstract: a b s t r a c tHydrogen separation with palladium-based membranes is considered as a promising technology for precombustion CO 2 capture as well as for industrial hydrogen production. With improvements in membrane permeance, resistances to mass transfer are becoming increasingly important. In this work, a systematic approach is followed in order to discern and account for different contributions to the overall mass transfer resistance, based on a combined experimental and modelling approach. Experiments have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
(46 reference statements)
1
27
0
1
Order By: Relevance
“…Concentration-driven hydrogen transport through Pd alloy membranes follows a series resistance mechanism which includes bulk flow resistance, Pd layer resistance, and porous support resistance. Additional mass transfer resistance can be present on the sweep side and in the porous support depending on sweep conditions [14][15][16]. For this study it is assumed that the sweep side will be operating under vacuum with negligible resistance, as would be expected for conditions in which almost pure hydrogen is required [15].…”
Section: Transport Model Developmentmentioning
confidence: 99%
“…Concentration-driven hydrogen transport through Pd alloy membranes follows a series resistance mechanism which includes bulk flow resistance, Pd layer resistance, and porous support resistance. Additional mass transfer resistance can be present on the sweep side and in the porous support depending on sweep conditions [14][15][16]. For this study it is assumed that the sweep side will be operating under vacuum with negligible resistance, as would be expected for conditions in which almost pure hydrogen is required [15].…”
Section: Transport Model Developmentmentioning
confidence: 99%
“…[24] showed that in mixtures of H 2 and N 2 the main resistance for H 2 transport across the membrane is concentration polarization (relative to membrane support, depletion and the membrane itself), but with the presence of other species, permeance inhibition becomes dominant. Several studies have presented a numerical simulation of mass and momentum balances for the permeance measurement application [19,25]. An approximation in the form of effective mass transfer coefficient (k c ) was suggested by [23] to account for their measurements, and its coefficient was determined experimentally and expressed in the form of a Sherwood number, as:…”
Section: Concentration Polarizationmentioning
confidence: 99%
“…At lower temperatures the CH 4 coverage is inhibited due to site blocking by hydrogen, but as the temperature increases the presence of more empty sites leads to higher CH 4 coverage, up to temperatures above 650 K where it starts to decline (Fig 8A and B). Table 1 Computed adsorption energies and calculated entropy change in T = 800 K [eV/ molecule] on a Pd(1 1 1) slab for possible inhibitors (after [25] Molecular methane adsorption was assumed to be non-activated. As can be seen in Fig.…”
Section: Permeance Inhibition and Atomistic Modelingmentioning
confidence: 99%
“…Within the CATO programme precombustion capture is examined as well. An example is the more fundamental work of Boon et al (2012) on the use of palladium membranes to separate hydrogen.…”
Section: Articles In Special Issuementioning
confidence: 99%